Adolescents in Peer Groups Make More Prudent Decisions When a Slightly Older Adult Is Present. (March 2016) - Silva, Karol; Chein, Jason; Steinberg, Laurence
Adolescents make more reckless decisions when with peers than when alone, which poses a challenge for organizations that place adolescents in situations in which risky and myopic decision making is problematic. We asked whether the effect of peers on adolescents' decision making is mitigated by the presence of a slightly older adult. We examined whether target subjects' risk taking was greater when they were in groups of 4 late-adolescent males (ages 18–22) than when they were in groups that mixed 3 late-adolescent males with 1 slightly older adult (age 25–30); risk taking in both of these conditions was compared with that of adolescents tested alone. We found that adolescents took more risks and expressed stronger preference for immediate rewards when they were grouped with 3 same-age peers than when they were alone. When 1 adolescent was replaced by someone slightly older, however, adolescents' decision making and reward processing resembled that seen when adolescents were tested alone. Adding a young adult to a work team of adolescents may improve group decision making.